Machine Learning Applications in Telecom and Banking - Bagam, Naveen; Shiramshetty, Sai Krishna; Mothey, Mouna; Annam, Sri Nikhil; Bussa, Santhosh (Integrated Journal for Research in Arts and Humanities, 2024)
The uses of machine learning (ML) in the banking and telecommunication sectors are investigated over the course of this research paper. The results of the article indicate that by means of enhanced customer experience, identification of fraudulent behaviour, risk management, and operational efficiency, machine learning algorithms are changing these sectors. This article covers several machine learning methods including supervised and unsupervised learning, deep learning, reinforcement learning, and others together with their particular uses in the banking and telecommunications sectors especially. To show how machine learning is affecting different sectors, case papers, real-world case studies, and samples abound. Furthermore included in the article are possible future trends and advancements in the field as well as the difficulties and restrictions related to the application of machine learning solutions.